FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT FEE PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Oktavia, Indri; Ningsih, Desrini (EDUTECH CONSULTANT, 2020)
Financial statements become an important part of a company that cannot be eliminated, because the for that the company must present financial statements properly and in accordance with accounting rules. Generally companies that have go public use the services of an Auditor external which results in an Audit fee that must be paid by the company. The amount of audit fees paid by companies varies each year. Some factors that can affect audit fees include company size, profitability, complexity and type of company ownership. Audit fee is a fee paid by the company to the auditor for services, time and energy services that have been issued for the examination of financial statements to be presented correctly. The company was conducted at banking companies listed on the Indonesian stock exchange in the 2014-2018 period. The sample collection method used is purposive sampling which is chosen based on certain criteria and researchers' considerations. The analysis method used in this study is multiple linear regression analysis using SPSS version 22. The results of this study indicate that company size has a significant effect on audit fee, while profitability, complexity and type of ownership have no significant effect on audit fee.